A REVIEW ON HERBO MINERAL FORMULATIONS CONTAINING LAUHA (IRON) W.S.R TO RASENDRA SARA SANGHRAHA (International Journal of Ayurveda and Pharma Research, 2018)
Rasendra Sara Sangraha is the oldest and most exhaustive treatise of Rasa Shastra, an important branch of Ayurveda, which revolutionised Ayurveda Pharmacopeia in the medieval period. It is one of classical works of 14th century period written by Sri Gopala Krishna Bhatt consists of 5 chapters with 2531 verses. Rasendra Sara Sangraha comprising the compilation of various times tested and therapeutically proved Rasayoga formulations. Lauha (iron) is a very essential element of the body system for treating many disease conditions as well as for physiological existence. Iron used as medicine from the Vedic period. Lauha preparations are extensively used from Acharya Charakas period in the form of Ayasruti and Navayasa loha. Rasendra Sara Sangraha has mentioned a total of 222 herbo mineral formulations having Lauha (iron). The present study deals with the chapter wise review of formulations of Rasendra Sara Sangraha containing Lauha as an ingredient mentioned in various disease conditions like Jwara, Arsas, krimi, Pandu, Soola, Pradara, Sodha and Gulma etc. These Lauha containing Herbo mineral Formulations has been elaborately compiled in 222 formulations.